IDENTIFICATION OF KNOWLEDGE OF BULLYING IN ADOLESCENTS AND ITS EFFECTS ON BEHAVIOR OF BULLYING FRIENDS - Nasir, Abdul; Rindayati, Rindayati; Iswatun, Iswatun; Mei Tyas, Anestasia Pangestu; Kurnia Putri, Bela Dwi (Journal of Vocational Nursing, 2020)
Introduction: Bullying behavior committed by fellow students at school is always associated with the search for self-identity and social status, but the behavior is very disturbing and has caused many victims. This study is to analyze the relationship of knowledge about bullying in adolescents and its influence on bullying behavior among peers. Methods: Data for this exploratory study were collected using a cross-sectional model. The study sample consisted of 80 students at SMAN 1 Kebomas Gresik who met the inclusion criteria. The independent variable is bullying knowledge. The dependent variable is bullying behavior. Two questionnaires were used in this study, knowledge about bullying and bullying behavior. The statistical test used is the Spearman Rank test with a significance level of α = 0.05.Results: the average sex of the respondent was 1.38 (SD: 0.487), the average age of the respondent was 1.90 (SD: 0.739), the average socioeconomic respondent was 2.75 (SD: 0.490), the average occupation of the respondent was 2.05 (SD: 0.525), the average bullying behavior of respondents is 1.40 (SD: 0.668), and there is a positive-negative relationship between knowledge and bullying behavior in adolescents (p = 0,000).Conclusion: increased knowledge about bullying can reduce bullying behavior. This is necessary for health education to improve understanding of the terror behaviors that are usually carried out by adolescents as a result of the moral release response from the growth and development process that is always experienced by adolescents so that they leave the knowledge possessed